Effects of the circulating environment of COVID-19 on platelet and neutrophil behavior - Fields, Alexander T.; Andraska, Elizabeth A.; Kaltenmeier, Christof; Matthay, Zachary A.; Herrera, Kimberly; Nuñez-Garcia, Brenda; Jones, Chayse M.; Wick, Katherine D.; Liu, Silvia; Luo, Jian-Hua; Yu, Yan-Ping; Matthay, Michael A.; et al. (Frontiers in Immunology, 2023)
Thromboinflammatory complications are well described sequalae of Coronavirus Disease 2019 (COVID-19), and there is evidence of both hyperreactive platelet and inflammatory neutrophil biology that contributes to the thromoinflammatory milieu. It has been demonstrated in other thromboinflammatory diseases that the circulating environment may affect cellular behavior, but what role this environment exerts on platelets and neutrophils in COVID-19 remains unknown. We tested the hypotheses that 1) plasma from COVID-19 patients can induce a prothrombotic platelet functional phenotype, and 2) contents released from platelets (platelet releasate) from COVID-19 patients can induce a proinflammatory neutrophil phenotype. We treated platelets with COVID-19 patient and disease control plasma and found that COVID-19 patient plasma promoted auto-aggregation, thereby reducing response to further stimulation ex-vivo. Neither disease condition increased the number of platelets adhered to a collagen and thromboplastin coated parallel plate flow chamber, but both markedly reduced platelet size. We treated healthy neutrophils with COVID-19 patient and disease control platelet releasate and found that COVID-19 patient platelet releasate increased myeloperoxidase-deoxyribonucleic acid complexes and induced changes to neutrophil gene expression. Together these results suggest aspects of the soluble environment of COVID-19 stimulate circulating platelets, and that the contents released from those platelets can elicit inflammatory neutrophil behavior independent of direct cellular contact.